Pengembangan Yoghurt berisi Lactobacillus rhamnosus dan Pediococcus pentosaceus dan Viabilitasnya selama Penyimpanan - Lilis Nuraida; Qamariyah Nurdin; Antung Sima Firlieyanti (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2014)
Yoghurt is a common vehicle to deliver probiotic bacteria. Compatibility between probiotics species is important for their survival during fermentation of yoghurt with multi probiotic bacteria. The aim of the research was to assess combination of Lactobacillus rhamnosus R23 and Pediococcus pentosa- ceus A38 in developing yoghurt. L. rhamnosus R23 and P. pentosaceus A38 isolated from breast milk were used as a single culture or in combination. Fermentation was carried out for 48 hrs at 37oC. Effect of inulin on the growth of those lactic acid bacteria was also evaluated. Sugar was added in formulation of yoghurt to improve its taste. L. rhamnosus R23 grew well on skim milk while P. pentosaceus A38 did not suf ciently acidi ed the milk. L. rhamnosus was detrimental to Pediococcus when they were used as combined starter cultures. Reasonable number of Pediococcus in yoghurt containing Lactobacillus and Pediococcus was reached by mixing yoghurt after fermentation by each bacteria separately. Addition of 15% sucrose gave the most preferred yoghurt. During 32 days of refrigerated storage, all yoghurt still maintained high num- ber of viable LAB (>8 log CFU/ml) with Pediococcus count of >6 log CFU/ml. During storage, pH value also declined but it was still above 4. Yoghurt containing L. rhamnosus and P. pentosaceus with different functional properties could be developed by fermenting the milk separately prior to mixing. Refrigerated storage of mixed yoghurt could retain the number of lactic acid bacteria for 32 days.